A Pathway for the Integration of Novel Ferroelectric Thin Films on Non-Planar Photonic Integrated Circuits - Enes Lievens; Kobe De Geest; Ewout Picavet; Liesbet Van Landschoot; Henk Vrielinck; Gilles Freddy Feutmba; Hannes Rijckaert; Klaartje De Buysser; Dries Van Thourhout; Peter Bienstman; Jeroen Beeckman (Micromachines)
The heterogeneous integration of ferroelectric thin films on silicon- or silicon nitride-based platforms for photonic integrated circuits plays a crucial role in the development of nanophotonic thin film modulators. For this purpose, an ultrathin seed film was recently introduced as an integration method for ferroelectric thin films such as BaTiO3 and Pb(Zr,Ti)O3. One issue with this self-orienting seed film is that for non-planarized circuits, it fails to act as a template film for the thin films. To circumvent this problem, we propose a method of planarization without the need for wafer-scale chemical mechanical polishing by using hydrogen silsesquioxane as a precursor to forming amorphous silica, in order to create an oxide cladding similar to the thermal oxide often present on silicon-based platforms. Additionally, this oxide cladding is compatible with the high annealing temperatures usually required for the deposition of these novel ferroelectric thin films (600–800 °C). The thickness of this silica film can be controlled through a dry etch process, giving rise to a versatile platform for integrating nanophotonic thin film modulators on a wider variety of substrates. Using this method, we successfully demonstrate a hybrid BaTiO3-Si ring modulator with a high Pockels coefficient of <semantics>rwg=155.57±10.91</semantics> pm V−1 and a half-wave voltage-length product of <semantics>VπL=2.638±0.084</semantics> V cm, confirming the integration of ferroelectric thin films on an initially non-planar substrate.